2010
DOI: 10.1523/jneurosci.0378-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Histamine Influences Body Temperature by Acting at H1and H3 Receptors on Distinct Populations of Preoptic Neurons

Abstract: The preoptic area/anterior hypothalamus, a region that contains neurons that control thermoregulation, is the main locus at which histamine affects body temperature. Here we report that histamine reduced the spontaneous firing rate of GABAergic preoptic neurons by activating H3 subtype histamine receptors. This effect involved a decrease in the level of phosphorylation of the extracellular signalregulated kinase and was not dependent on synaptic activity. Furthermore, a population of non-GABAergic neurons was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
124
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(130 citation statements)
references
References 43 publications
6
124
0
Order By: Relevance
“…Other antihistamine drugs such as loratadine and cyproheptadine are also associated with increased body weight and hyperplasia [70][71][72][73]. Furthermore, the H 1 R antagonistic affinity of SGAs contributes to fat accumulation via downregulation of lipolysis, while upregulating lipogenesis in white adipose tissue [74][75][76][77].…”
Section: H 1 R H 3 R and Sga-induced Weight Gainmentioning
confidence: 99%
“…Other antihistamine drugs such as loratadine and cyproheptadine are also associated with increased body weight and hyperplasia [70][71][72][73]. Furthermore, the H 1 R antagonistic affinity of SGAs contributes to fat accumulation via downregulation of lipolysis, while upregulating lipogenesis in white adipose tissue [74][75][76][77].…”
Section: H 1 R H 3 R and Sga-induced Weight Gainmentioning
confidence: 99%
“…[19,[37][38][39] Microinjection of histamine into the PVN or preoptic area (POA), which are important regions controlling BAT thermoregulation via the sympathetic nervous system, significantly activated BAT sympathetic activity and increased BAT uncoupling protein 1 (UCP-1) mRNA expression in rats. [38] The POA, which is a main region for histamine regulating body temperature, sends outflows to the rostral raphe pallidus (rRPa) that contains sympathetic premotor neurons to regulate BAT thermogenesis (reviewed in [40] ).…”
Section: The Role Of Histamine and H1 Receptors In Energy Expenditurementioning
confidence: 99%
“…Intra-MnPO (median preoptic nucleus) injection of histamine and an H1 receptor agonist, 2-pyridylethylamine, significantly induced hyperthermia without increasing motor activity in mice. [39] Studies also suggest that activation of H1 receptors expressed on glutamatergic neurons in the MnPO activates BAT thermogenesis by stimulating sympathetic neurons in the rRPa. [39,41] Additionally, in the medial preoptic nucleus (MPON), H1 receptor activation on the glutamatergic neurons also significantly regulates body temperature, although H2…”
Section: The Role Of Histamine and H1 Receptors In Energy Expenditurementioning
confidence: 99%
“…This finding may reflect technical limitations or the fact that PO/AH neurons send few local projections [28]. Our studies in mice have not found evidence for local projections of PO/AH GABAergic neurons but have revealed reciprocal connections of PO/AH glutamatergic neurons [21].…”
Section: Thermoregulatory Neuronal Network Comprising Po/ah Thermosementioning
confidence: 57%
“…Recent studies have established also the existence of direct glutamatergic projections from the PO/AH [20,21] as well as from the lateral hypothalamus [22] to the rRPA that control thermoregulation. Some glutamatergic PO/AH neurons projecting to rRPa are also peptidergic [20].…”
Section: Thermoregulatory Neuronal Network Comprising Po/ah Thermosementioning
confidence: 99%